Meningkatkan Keterampilan Berpikir Kreatif Pada Pembelajaran IPAS Melalui Model Think Pair Share Dengan Berbantuan Piramida Bergambar - Sa'diyah, Chalimatus; Rasidi, Rasidi; Rahmawati, Puji; Andriyani, Novi (Universitas Negeri Makassar, 2024)
This research was conducted at SD N Experiment 2 because the level of students' creative thinking skills was still considered low. This can be shown that there are still many students who do not dare to express their opinions. The aim of this research was to improve students' creative thinking skills in science learning. This research is in the form of classroom action research with 4 stages, namely: Planning, Implementation, Observation and Reflection carried out in 2 learning cycles consisting of 2 meetings. Obtaining data through observations or observations and scores from evaluation test results. The subjects of this research were 28 students in class 5A of SD N Experiment 2. Based on the research results, it can be concluded that there was an increase in students' creative thinking skills from pre-cycle of 25.8% with poor criteria and increased in cycle 1 with a gain of 60.7% with fairly good criteria, and increased again in cycle 2 with a gain of 85.9%. % with very good criteria. By carrying out this classroom action research, it is hoped that it will be able to improve creative thinking skills not only in science learning but also in learning other subjects.